PENDEKATAN PEMBELAJARAN BERBASIS MASALAH DI SD - Iradamayanti (CV. ADIBA AISHA AMIRA, 2026)
Problem-based learning (PBL) is an innovative learning approach that is oriented towards developing students' critical thinking skills, problem solving and learning independence. This research aims to examine the concept, implementation, advantages, challenges and relevance of problem-based learning with the Independent Curriculum in Elementary Schools. The research method used is library research by collecting and analyzing various relevant literature sources, such as books and scientific journals. The results of the study show that PBL is able to increase student involvement in learning, deepen understanding of concepts, and develop higher order thinking skills. Apart from that, PBL also supports the development of cooperation, communication and independent learning skills through the presentation of contextual problems. However, in its implementation there are still several obstacles, such as limited teacher readiness, limited time allocation, characteristics of elementary school students, as well as limited facilities and infrastructure. On the other hand, PBL has strong relevance to the Independent Curriculum because it is in line with the principles of student-centered learning and strengthening the Pancasila Student Profile. Thus, problem-based learning can be an effective alternative learning strategy in improving the quality of education in elementary schools if it is supported by careful planning and adequate teacher competence.